Urologic Prostheses The Complete Practical Guide to Devices, Their Implantation, and Patient Follow Up - Carson, Culley C. (Current Clinical Urology, 2002)
Today, implanted artificial prosthetic devices as substitutes for damaged or poorly functioning tissue structures are no longer uncommon when treating a variety of urologic problems and disorders. In Urologic Prostheses: The Complete Practical Guide to Devices, Their Implantation, and Patient Follow Up, a team of authoritative urologic surgeons reviews the latest advances in urologic prosthetic surgery and the patient management techniques needed to successfully implement them. These highly experienced clinicians fully describe each technique and process, providing proven guidelines for patient evaluation prior to its use, its surgical implantation, and postoperative treatment of the patient. The topics expertly covered range from injectable materials used in a variety of circumstances to artificial urinary sphincters, from urethral stents, penile implants, and testicular and penile prostheses, to the newer penile rigidity systems. Comprehensive and authoritative, Urologic Prostheses: The Complete Practical Guide to Devices, Their Implantation, and Patient Follow Up offers both new and experienced practitioners of urologic prosthetic surgery a clear, concise, and practice-oriented survey of all the therapeutic options now available, as well as a guide to today's standard-of-care treatments for these patients